The Role of Investor Behavior in Forming Abnormal Return - An Economic Perspective - Ariskha, Nisma; Amiruddin, Amiruddin; Alam, Syamsu (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to conduct a comprehensive analysis of macroeconomic factors influencing abnormal returns and the role of investor behavior in shaping them. Utilizing a systematic literature review, the study is based on the identification of 39 Scopus-indexed articles published between 2014 and 2024, ranging from Quartile Q1 to Q4. The review explores prior research on abnormal returns to identify key findings, macroeconomic factors impacting abnormal returns, and the role of investor behavior in their formation. Using the Research Plan Systematic Literature Review menu in the Watase application, the term